Promoting Computational Thinking through Programming Trends, Tools, and Educational Approaches: a Systematic Review - Irawan, Edi; Rosjanuardi, Rizky; Prabawanto, Sufyani (Universitas Muhammadiyah Mataram, 2024)
This systematic research aims to provide a comprehensive overview of the development of analysis related to the use of programming in the development of Computational Thinking (CT), especially in the context of education from primary to tertiary levels. This study analyzed 88 articles from empirical studies related to the use of programming to develop CT sourced from the Scopus database. The analysis process followed the PRISMA 2020 guidelines and consisted of three stages: search, selection, and data analysis. Descriptive and thematic statistical approaches were used for data analysis. Instruments used in the selection of articles included Rayyan for screening based on inclusion criteria, as well as Microsoft Excel for coding and thematic analysis. The results showed that articles related to the use of programming to promote CT have appeared since 2011 but have increased significantly since 2016, with an annual growth rate of 17.6%. Most studies used quantitative approaches, followed by qualitative and mixed methods. Overall, 270 authors from 27 countries contributed to the study, with the United States having the highest number of publications. A total of 33 programming tools were identified, with Scratch being the most widely used tool, followed by Blockly, LEGO, Scratch Jr., Code.org, Python, Alice, App Inventor, Kodu, R, MakeCode, and Arduino. Scratch Jr. is most commonly used at the early childhood education level, while programming languages such as Python, R, and MATLAB are more commonly used in higher education. The implications of these findings suggest that the trend of using programming tools such as Scratch and Blockly has the potential to influence CT teaching strategies in the classroom, as well as the importance of using varied programming tools in efforts to integrate CT into the education curriculum.